A comparison of the various equations published for the estimation of characteristics of hen's eggs, the importance of reporting the compression rate for shell strength measurements, and distinction between egg specific gravity and density. Issue 2 (3rd April 2022) - Hamilton, R. M. G.
SUMMARY: Prediction equations allow the estimation of dependent variable from the value obtained from the measurements of an independent variable. Comparisons of estimates obtained for of 85 equations that were published for the prediction of shell strength parameters were made. Egg weight, specific gravity, length, width and thickness were the independent factors use to estimate surface area (SA), egg volume (EV), shell weight, percent shell, sphericity, thickness, compression and impact fracture strength, and shape index. Values (n = 5–20) from published results were used to create a data set for the testing of these equations. Comparisons, based on coefficient of variation (CV), among the calculated estimates obtained with the majority of the equations (72) showed the variability was small, especially those for SA and EV, However, the CV for other equations (7) showed their estimates varied over wide range; whereas, the estimates for the remainder (6) were outside the expected acceptable range. Ten equations, as published, required an 'adjustment factor', either multiplication or division, in order to produce an estimate that was within the expected range. It is essential that the rate of compression used to measure compression fracture strength of egg shell be reported because, since the egg shell is a brittle material, the value obtained when fracture strength is measured by compression is dependent on the compression rate. Without knowing the compression rate, it is not possible to establish whether the difference among published shell strength measurements is actual or due to differences in compression rates. There is a need to clarify that the 'saline flotation method' measures the density of the egg, NOT specific gravity. In addition, the use of various abbreviations for the same shell strength variable causes confusion that could be clarified by the development of standardised abbreviations. Finally, more care is needed to ensure the original authors are cited when reporting the sources of prediction equations. Abbreviations : EW: egg weight; SW: shell weight; EV: egg volume; SA: surface area; L: longitudinal length; W: axial width (diameter); SG: specific gravity; STk: shell thickness; sd: standard deviation; obs: observational; CFS: quasi-static compression fracture strength; DFm: non-destructive deformation; SW/SA: shell weight per unit surface area; Dg : geometric diameter; SI: shape index; μm: micro metre; N: Newton; n: number of observations; CV: coefficient of variation